Yrast and nonyrast states in Te 126 - Dey A.; Singh A.K.; Basu A.; Nag S.; Mukherjee G.; Bhattacharyya S.; Nandi S.; Bhattacharya S.; Banik R.; Raut R.; Ghugre S.S.; Das S.; Samanta S.; Chatterjee S.; Goswami A.; Ali S.; Pai H.; Rajbanshi S. (My University, 2025)
The yrast and nonyrast states of Te126 were populated in a fusion-evaporation reaction using a target of Sn124 and α beam at 31 MeV energy. All the γ-γ coincidences were recorded using the Indian National Gamma Array at the Variable Energy Cyclotron Centre, India, and processed by a digital data-acquisition system. The level scheme was enriched with the addition of 65 new transitions and the identification of five new structures. Spin and parity assignments were made and the subsequent results were interpreted in the framework of the nuclear shell model using the large-scale shell-model code antoine. © 2024 American Physical Society.